Noninvasive photoacoustic and fluorescent tracking of optical dye labeled T cellular activities of diseased sites at new depth. Issue 9 (24th May 2018) - Zheng, Shuai; Li, Honghui; Lai, Kejiong; Chen, Maomao; Fu, Guofeng; Liu, Wen‐Hsien; Fu, Guo; Nie, Liming
Abstract : The migration of immune cells is crucial to the immune response. Visualization of these processes has previously been limited because of the imaging depth. We developed a deep‐penetrating, sensitive and high‐resolution method to use fast photoacoustic tomography (PAT) to image the dynamic changes of T cells in lymph node and diseases at new depth (up to 9.5 mm). T cells labeled with NIR‐797‐isothiocyanate, an excellent near‐infrared photoacoustic and fluorescent agent, were intravenously injected to the mice. We used fluorescence imaging to determine the location of T cells roughly and photoacoustic imaging is used to observe T‐cell responses in diseased sites deeply and carefully. The dynamic changes of T cells in lymph node, acute disease (bacterial infection) and chronic disease (tumor) were observed noninvasively by photoacoustic and fluorescence imaging at different time points. T cells accumulated gradually and reached a maximum at 4 hours and declined afterwards in lymph node and bacterial infection site. At tumor model, T cells immigrated to the tumor with a maximum at 12 hours. Our study can not only provide a new observing method for immune activities tracking, but also enable continuous monitoring for therapeutic interventions. Abstract : We developed a deep‐penetrating, high‐resolution, high‐sensitivity and fast photoacoustic tomography (PAT) to image the migration of NIR‐797 labeled T cells in lymph node, listeriosis and tumor at new depth (up to 9.5 mm). Our study can not only provide a new observing method for immune activities tracking in deep tissue in vivo, but also enable continuous monitoring for therapeutic interventions.